2022
DOI: 10.3389/fnagi.2022.880167
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Link Between ERUPR Signaling and MicroRNA in Pathogenesis of Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) is a neurodegenerative proteinopathic disease. The deposits of misfolded Amyloid β and Tau proteins in the brain of patients with AD suggest an imbalance in endoplasmic reticulum (ER) proteostasis. ER stress is due to accumulation of aberrant proteins in the ER lumen, which then leads to activation of three sensor protein pathways that ultimately evokes the adaptive mechanism of the unfolded protein response (UPR). The UPR mechanism operates via adaptive UPR and the apoptotic UPR. Adap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…Interestingly, MicroRNAs (miRNAs) are non-coding 19–25 nucleotides long, single-stranded protein molecules that are endogenously synthesized and evolutionarily conserved [ 11 , 12 ]. The role of miRNAs is imperative in several cellular processes, such as cellular proliferation, cell differentiation, apoptosis, and in neural cell biology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, MicroRNAs (miRNAs) are non-coding 19–25 nucleotides long, single-stranded protein molecules that are endogenously synthesized and evolutionarily conserved [ 11 , 12 ]. The role of miRNAs is imperative in several cellular processes, such as cellular proliferation, cell differentiation, apoptosis, and in neural cell biology.…”
Section: Introductionmentioning
confidence: 99%
“…The role of miRNAs in regulating endoplasmic reticulum (ER) stress is the foundation to unravel, following several studies. Several miRNA families, for instance miR-485, were found to be dysregulated in AD and other neurological diseases [ 11 , 12 , 13 ]. Notably, miRNAs exhibit a crucial role in the pathogenesis of several neurodegenerative diseases, such as AD; they may be either upregulated or downregulated in AD.…”
Section: Introductionmentioning
confidence: 99%
“…ER stress is a response process in which cells activate a series of signaling pathways in response to conditions such as the accumulation of misfolded and unfolded protein and the dysregulation of calcium homeostasis, which have been observed in neurodegenerative diseases such as Parkinson's disease, Alzheimer's disease, and so on. 49 51 GRP78/Bip protein is considered to be the primary sensor and master regulator of he ER stress; it is localized to membranous structures and is seen on the nuclear membrane and ER in retinal neurons and glial cells at the subcellular level. 52 , 53 As an ER chaperone, GRP78/Bip overexpression can indicate occurrence of the unfolded protein response (UPR), which maintains protein homeostasis and promotes cell survival.…”
Section: Discussionmentioning
confidence: 99%
“…Obvious possible candidates include neurodegenerative diseases such as Parkinson's disease, Alzheimer's disease, Huntington's disease, and Creutzfeld-Jacob disease. The role of intracellular Ca 2+ in general and of ER Ca 2+ in particular (Ureshino et al, 2019;da Costa et al, 2020;Lim et al, 2021;Callens et al, 2021;Kovacs et al, 2021;Guan et al, 2021;Huang et al, 2022;Ge et al, 2022;Kim et al, 2022) as well as of ER stress and accumulation of misfolded proteins (da Costa et al, 2020;Guan et al, 2021;Kim et al, 2022;Ren et al, 2021;Yasmeen et al, 2022;Shacham et al, 2019;Chakraborty et al, 2005) have indeed already been demonstrated in several neurodegenerative diseases.…”
Section: Future Perspectives and Concluding Remarksmentioning
confidence: 99%